LEVERAGING TIKTOK ADVERTISING AND EWOM: EXPLORING THE MODERATING ROLE OF EXPERIENTIAL VALUE ON CONSUMER BUYING BEHAVIOR - Farahdiba, Dea (DAS Institute, 2024)
The rising popularity of TikTok among young audiences has drawn marketers' attention to its potential as a platform for clothing product advertising. However, capturing consumer focus on a single product amidst the vast content on TikTok remains challenging. Additionally, negative perceptions of clothing product value may deter consumers from engaging in buying behavior. This study aims to examine the influence of TikTok social media advertising and electronic word-of-mouth (eWOM) on consumer buying behavior, with experiential value serving as a moderating variable. Employing the Unified Theory of Acceptance and Use of Technology (UTAUT2) framework, this research adopts a quantitative approach with a survey method. Data were collected from 406 respondents via questionnaires and analyzed using the path analysis method in SmartPLS 3. The findings reveal that TikTok advertising significantly impacts consumer buying behavior, whereas eWOM about clothing products does not directly affect buying behavior. Experiential value moderates and strengthens the relationship between TikTok advertising and eWOM on consumer buying behavior